Fulton Mall Free Speech Area Rally Opposing Proposition 41 - Watkins, Howard::::::::: (1984)
Fresno County Judy Andreen on Free Speech stage speaking against Proposition 41 Opponents of Proposition 41 sitting on benches listening to her; Michael Kanz in burgundy swearer on far right